Mesenchymal Stem Cells for Cartilage Regeneration of TMJ Osteoarthritis - Dixin Cui; Hongyu Li; Xin Xu; Ling Ye; Xuedong Zhou; Liwei Zheng; Yachuan Zhou (Stem Cells International)
Temporomandibular joint osteoarthritis (TMJ OA) is a degenerative disease, characterized by progressive cartilage degradation, subchondral bone remodeling, synovitis, and chronic pain. Due to the limited self-healing capacity in condylar cartilage, traditional clinical treatments have limited symptom-modifying and structure-modifying effects to restore impaired cartilage as well as other TMJ tissues. In recent years, stem cell-based therapy has raised much attention as an alternative approach towards tissue repair and regeneration. Mesenchymal stem cells (MSCs), derived from the bone marrow, synovium, and even umbilical cord, play a role as seed cells for the cartilage regeneration of TMJ OA. MSCs possess multilineage differentiation potential, including chondrogenic differentiation as well as osteogenic differentiation. In addition, the trophic modulations of MSCs exert anti-inflammatory and immunomodulatory effects under aberrant conditions. Furthermore, MSCs combined with appropriate scaffolds can form cartilaginous or even osseous compartments to repair damaged tissue and impaired function of TMJ. In this review, we will briefly discuss the pathogenesis of cartilage degeneration in TMJ OA and emphasize the potential sources of MSCs and novel approaches for the cartilage regeneration of TMJ OA, particularly focusing on the MSC-based therapy and tissue engineering.